Pengaruh Pengelolaan Kelancaran Proses Produksi terhadap Kualitas Produk Migas yang dimoderasi Peran Laboratorium - Dedi Setiadi Miharja; Iwan Sidharta (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
The oil and gas industry is a driver of the country's economy. The availability of oil and gas products is related to the quality of the product. This study aims to examine the role of laboratories in moderating the influence of the continuous production process on the quality of oil and gas products. Positivism approach is carried out by surveying supervisor level employees with stratified random sampling technique. Hypothesis testing is done by structuring equation modeling approach. The results of the study prove there is a moderating influence of the role of the laboratory in improving the quality of oil and gas products through a continuous production process.